2015
DOI: 10.5296/ijafr.v5i2.8258
|View full text |Cite
|
Sign up to set email alerts
|

Stock Price Adjustment to Corporate Accounting Disclosure: A Quantitative Study on Dhaka Stock Exchange (DSE), Bangladesh.

Abstract: This study has been designed to detect whether corporate accounting disclosures through annual report influence stock price movement in Dhaka Stock Exchange. To conduct our study, we gathered a series of panel data from 2010 through 2014 of 25 private commercial banks. Least square regression analysis has been done by incorporating fixed effect and random effect models and six models have been developed through Hausman Test. The resulting output revealed that “Earning per share”, “Return on equity” and “Net as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
4
3
0
Order By: Relevance
“…The variables that depicted high level of colinearity were not dropped from the model because these are important variables to investors as well as to banking industry. These results are consistent with the findings of [53] and are contrary to [50].…”
Section: Correlation Matrix Analysis and Multi-collinearitysupporting
confidence: 92%
“…The variables that depicted high level of colinearity were not dropped from the model because these are important variables to investors as well as to banking industry. These results are consistent with the findings of [53] and are contrary to [50].…”
Section: Correlation Matrix Analysis and Multi-collinearitysupporting
confidence: 92%
“…This indicates that Net Operating Cash Flow influences the share price significant positively. The results also revealed that NAVPS was positively correlated with the share's market value at a 1% significance level supporting Halonen et al (2013); Tharmila and Nimalathasan (2013) and Ghosh and Ghosh (2015) but varying from Miah (2012). Investors want to ensure sufficient NAVPS to maximize wealth of the company.…”
Section: Discussionsupporting
confidence: 74%
“…The Beta coefficient of NAVPS is 3.963, with a p-value of 0.000 statistically significant at 1% level. It also means the NAVPS statistically significant impact on the share price supporting Halonen et al (2013); Tharmila and Nimalathasan (2013) and Ghosh and Ghosh (2015) but varying from Miah (2012). The beta coefficient of EPS is -3.650 with a p-value of 0.100 statistically significant at 10% level.…”
Section: Regression Analysissupporting
confidence: 55%
See 2 more Smart Citations